Tolaki Customary Law Regulation on Tolaki Community Land Disputes in Lambandia District, East Kolaka Regency - Gilang Ramadhan, Purnama; Akib, Ma'ruf; Wahyudi Umar (Universitas Muhammadiyah Surakarta, 2024)
Customary land is an essential aspect of the Tolaki tribal community, which is jointly owned by them and holds great significance. However, disputes over customary land often arise, leading to compliance with customary law and its consequences. This research seeks to explore the views and regulations of Tolaki customary law regarding land disputes and conflicts. The doctrinal legal research approach has been used in this research to understand how land disputes are handled under Tolaki customary law. The results indicate that land disputes are considered a form of social conflict that arises due to violations of customary civil law. The resolution process involves a series of customs, and a solution is reached through positive laws. The Tolaki customary law has laid down several principles that guide the resolution process of land disputes. According to their customs, the disputing parties must first attempt to resolve the matter through negotiations. If negotiations fail, the parties must seek the help of their respective customary leaders, who will then guide them through the dispute resolution process. If the dispute remains unresolved, then the parties may seek the intervention of positive law. In conclusion, the Tolaki customary law views land disputes as a social conflict that can be resolved through a series of customs and positive laws. It is imperative to preserve these customs and laws to maintain the sanctity of customary land and ensure that disputes are resolved fairly. Tanah adat merupakan aspek penting bagi masyarakat suku Tolaki, yang dimiliki bersama dan memiliki arti penting. Namun, sengketa atas tanah adat sering kali muncul, yang mengarah pada kepatuhan terhadap hukum adat dan konsekuensinya. Penelitian ini bertujuan untuk mengeksplorasi pandangan dan pengaturan hukum adat Tolaki mengenai sengketa dan konflik tanah. Pendekatan penelitian hukum doktrinal telah digunakan dalam penelitian ini untuk memahami bagaimana sengketa tanah ditangani di bawah hukum adat Tolaki. Hasil penelitian menunjukkan bahwa sengketa tanah dianggap sebagai bentuk konflik sosial yang muncul akibat pelanggaran hukum perdata adat. Proses penyelesaiannya melibatkan serangkaian adat istiadat, dan penyelesaiannya dilakukan melalui hukum positif. Hukum adat Tolaki telah menetapkan beberapa prinsip yang memandu proses penyelesaian sengketa tanah. Menurut adat istiadat mereka, pihak-pihak yang bersengketa harus terlebih dahulu berusaha menyelesaikan masalah melalui negosiasi. Jika negosiasi gagal, para pihak harus mencari bantuan dari pemimpin adat masing-masing, yang kemudian akan memandu mereka melalui proses penyelesaian sengketa. Jika sengketa tetap tidak terselesaikan, maka para pihak dapat meminta intervensi hukum positif. Kesimpulannya, hukum adat Tolaki memandang sengketa tanah sebagai konflik sosial yang dapat diselesaikan melalui serangkaian hukum adat dan hukum positif. Sangat penting untuk melestarikan adat dan hukum ini untuk menjaga kesucian tanah adat dan memastikan bahwa perselisihan diselesaikan secara adil.